2009
DOI: 10.1063/1.3103884
|View full text |Cite
|
Sign up to set email alerts
|

Turbulence statistics and structures of drag-reducing turbulent boundary layer in homogeneous aqueous surfactant solutions

Abstract: In our earlier work ͓Itoh et al., Phys. Fluids 17, 075107 ͑2005͔͒, the additional maximum of the streamwise turbulence intensity near the center of the drag-reducing turbulent boundary layer was found in the homogeneous dilute aqueous surfactant solution which was a mixture of cetyltrimethyl ammonium chloride with sodium salicylate as counterion. In this work, we systematically investigated the influence of the drag-reducing surfactant on the velocity fields of the turbulent boundary layer at various Reynolds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

21
63
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(84 citation statements)
references
References 45 publications
(64 reference statements)
21
63
0
Order By: Relevance
“…The time averaged product of these two velocity fluctuations at any point in the turbulent flow are called the Reynolds stress which is the major component of the local stress in the turbulent region away from the wall. In strongly drag reducing flows these two velocity fluctuations are nearly completely decoupled [6,7] and the resultant lowered Reynolds stress in the turbulent core, along with lower velocity gradient in the near wall region result in large decreases in drag (drag reduction). It was hypothesized by Gyr and Bewerdorff [5] and by Hu and Matthys [8] that for threadlike micelles aligned with the flow, elongational flow is more effective in producing micelle growth than shear flow as it favors side to side collision between micelles causing the micelles to grow in size after collision through fusion.…”
Section: Introductionmentioning
confidence: 97%
“…The time averaged product of these two velocity fluctuations at any point in the turbulent flow are called the Reynolds stress which is the major component of the local stress in the turbulent region away from the wall. In strongly drag reducing flows these two velocity fluctuations are nearly completely decoupled [6,7] and the resultant lowered Reynolds stress in the turbulent core, along with lower velocity gradient in the near wall region result in large decreases in drag (drag reduction). It was hypothesized by Gyr and Bewerdorff [5] and by Hu and Matthys [8] that for threadlike micelles aligned with the flow, elongational flow is more effective in producing micelle growth than shear flow as it favors side to side collision between micelles causing the micelles to grow in size after collision through fusion.…”
Section: Introductionmentioning
confidence: 97%
“…A detailed discussion of this bilayer structure will be given in another section. In the case of turbulent boundary flow, a characteristic distribution of the streamwise velocity fluctuation was also observed in the drag-reducing flow [19,20]. However, the detailed structure of these peaks has not been discussed.…”
Section: Turbulent Intensitymentioning
confidence: 99%
“…They also categorized Reynolds number dependence on the drag-reduction into four flow regimes considering that the drag-reduction rate and turbulent statistics were different in each regime, despite similar drag-reduction rates. Itoh and Tamano [19] and Tamano et al [20] investigated the influence of the drag-reducing flow with surfactant additives on the velocity fields of the turbulent boundary layer using a two-component LDV and PIV. They found the existence of the additional maximum of the streamwise turbulent intensity near the center of the boundary layer.…”
Section: Introductionmentioning
confidence: 99%
“…In our recent work (Tamano et al 2010), we investigated not only the drag reduction ratio, which was obtained by measuring the pressure drop and flow rate in the pipe flow of non-ionic surfactant solutions, but also the drag-reducing effect on the development of a turbulent boundary layer using two-component laser-Doppler velocimetry (LDV) and particle image velocimetry (PIV) systems. Turbulence statistics and structures for non-ionic surfactant solutions showed the behaviour of typical drag-reducing flow, such as suppression of turbulence and modification of near-wall vortices, but they were different from those of drag-reducing cationic surfactant solutions (see Tamano et al 2009bTamano et al , 2010. They showed that turbulence statistics for turbulent boundary layers of non-ionic surfactant solutions were similar to those for polymer solutions, rather than cationic solutions, in which bilayered structures of the fluctuating velocity vectors were observed in high activity.…”
mentioning
confidence: 98%